Emerging investigator series: membrane distillation and high salinity: analysis and implications. Issue 6 (6th May 2020) - Hardikar, Mukta; Marquez, Itzel; Achilli, Andrea
Abstract : In energy efficient membrane distillation, the low transmembrane temperature difference exacerbates salinity's effect on water flux and specific energy consumption. Abstract : Membrane distillation (MD) is a desalination technology where the main driving force for production of water/distillate is the vapor pressure gradient across the membrane. This principle makes the water flux in MD theoretically a weak function of salinity. However, several pilot-scale experiments treating high salinity water (up to 220 g L −1 NaCl) have reported a marked decline in water flux with increase in salinity, although this was not always reported in bench-scale experiments. In this paper, a literature review on bench- and pilot-scale MD studies conducted at high salinities is presented to highlight the reasons why salinity matters in MD. Increase in salinity results in a reduction in water vapor pressure and hence driving force across the membrane, which may even reverse the direction of water flux. The challenges in using bench-scale results and their implications in a scaled-up MD set-up are also reviewed. As pilot-scale systems are designed to be energy efficient, the transmembrane temperature differences are markedly smaller than bench-scale conditions and the operating temperature conditions to achieve forward water flux are heavily dependent on the salinity of the water being treated. This has implications on the energy requirements of an MD system as a minimum transmembrane temperature difference needs to be maintained at a given feed salinity for water production. This feature highlights the relationship between salinity and energy consumption in MD. The minimum transmembrane temperature difference to achieve non-zero water flux dictates the minimum energy requirements of an MD pilot-scale set-up treating high salinity water.